1972
DOI: 10.1128/am.23.2.262-267.1972
|View full text |Cite
|
Sign up to set email alerts
|

Structures Suggesting Cell-Wall-Deficient Forms Detected in Circulating Erythrocytes by Fluorochrome Staining

Abstract: Cell-wall-deficient (CWD) forms of bacteria are associated with certain cases of idiopathic septicemia. In this preliminary study of blood examined immediately after venipuncture, structures with a morphology characteristic of CWD forms were seen parasitizing the erythrocytes. These inclusions were usually circumferential, but in some cases they protruded from the red cells. The CWD forms were detected by staining with Gould's rhodamine-labeled muramidase, which reacted similarly to acridine orange but with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is supposed that the life cycle of blood microbiota encompass intracellular proliferation mainly in leukocytes and erythrocytes. Documented evidence by Pohlod et al (1972) indicated the presence of cell-wall deficient microbial forms in circulating erythrocytes by fluorochrome staining. The authors examined freshly drawn blood and described structures, which appear to be microbial, extended in rhizoid filaments from the erythrocytes (Pohlod et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is supposed that the life cycle of blood microbiota encompass intracellular proliferation mainly in leukocytes and erythrocytes. Documented evidence by Pohlod et al (1972) indicated the presence of cell-wall deficient microbial forms in circulating erythrocytes by fluorochrome staining. The authors examined freshly drawn blood and described structures, which appear to be microbial, extended in rhizoid filaments from the erythrocytes (Pohlod et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the life cycle of blood microbiota encompass intracellular proliferation mainly in leukocytes and erythrocytes. Documented evidence by Pohlod et al. (1972) indicated the presence of cell-wall deficient microbial forms in circulating erythrocytes by fluorochrome staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has implicated L-form bacteria with disease 53,54 as well as shown an association with erythrocytes. 55 The Aquabacterium-specific primers resulted in amplification of 16S rRNA sequences in more samples than the 16S universal primers. The Aquabacterium-specific primers, because of their specificity, will be more sensitive in detecting the presence of Aquabacterium DNA than 16S rRNA universal primers.…”
Section: Discussionmentioning
confidence: 99%